ELISA GIACCARDI, ed., Heritage and Social Media: Understanding Heritage in a Participatory Culture - Sheffield, Rebecka (Archivaria, 2013)
Heritage and Social Media: Understanding Heritage in a Participatory Culture. ELISA GIACCARDI, ed. New York: Routledge, 2012. xvii, 251 pp. ISBN 978-0-415-61667-6.